2001
DOI: 10.4049/jimmunol.167.7.3555
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Role of Toll-Like Receptor 9 in CpG DNA-Induced Activation of Human Cells

Abstract: Unmethylated CpG motifs present in bacterial DNA stimulate a rapid and robust innate immune response. Human cell lines and PBMC that recognize CpG DNA express membrane-bound human Toll-like receptor 9 (hTLR9). Cells that are not responsive to CpG DNA become responsive when transfected with hTLR9. Expression of hTLR9 dramatically increases uptake of CpG (but not control) DNA into endocytic vesicles. Upon cell stimulation, hTLR9 and CpG DNA are found in the same endocytic vesicles. Cells expressing hTLR9 are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
370
3
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(385 citation statements)
references
References 21 publications
10
370
3
2
Order By: Relevance
“…This suggests that TLR9 is not sufficient for transducing the A/D-type CpG DNA signal, and that another molecule(s) cooperatively functions to induce IFN-␣ production with TLR9. It is assumed that oligodeoxynucleotides are incorporated into cells through a pathway not requiring any specific sequences and that only CpG DNAs can bind to TLR9 and trigger TLR9 signaling in the endosome (10,28). However, confocal microscopic analysis revealed that conventional and A/D-CpG DNAs are destined for different cell compartments (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that TLR9 is not sufficient for transducing the A/D-type CpG DNA signal, and that another molecule(s) cooperatively functions to induce IFN-␣ production with TLR9. It is assumed that oligodeoxynucleotides are incorporated into cells through a pathway not requiring any specific sequences and that only CpG DNAs can bind to TLR9 and trigger TLR9 signaling in the endosome (10,28). However, confocal microscopic analysis revealed that conventional and A/D-CpG DNAs are destined for different cell compartments (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLR9 expression is sufficient to confer responsiveness to CpG DNA on a human kidney cell line (9,10). Some CpG DNAs can activate human immune cells more efficiently than murine ones, while others can activate murine cells more effectively than human ones.…”
mentioning
confidence: 91%
“…TLR9 recognizes viral CpG sequences and induces the induction of IFN-a (Takeshita et al, 2001;Lund et al, 2003;Krug et al, 2004). However, as membrane restriction prevents TLRs from sampling the cytosol where much of the viral life cycle occurs, cytosolic PRRs provide comprehensive innate immune recognition.…”
Section: Viral Recognitionmentioning
confidence: 99%
“…10) Next we examined Fgf23 expression in BMDCs treated with Pam3CSK4 and CpG-ODN, which are known ligands for TLR2 and TLR9, respectively. 10,13,14) Treatment with 0.5 µg/mL Pam3CSK4 significantly increased Fgf23 expression in BMDCs. Fgf23 expression in BMDCs treated with 1 µM CpG-ODN was slightly increased by about 1.7 times but not significantly (Fig.…”
Section: Fig 2 Expression Of Fgf23 In Immune Tissues and Cells (A) mentioning
confidence: 99%